Holocene landscape evolution of an estuarine wetland in relation to its human occupation and exploitation: Waasland Scheldt polders, northern Belgium. Issue 1 (30th August 2016) - Missiaen, T.; Jongepier, I.; Heirman, K.; Soens, T.; Gelorini, V.; Verniers, J.; Verhegge, J.; Crombé, Ph.
Abstract: This paper describes the landscape evolution of the Waasland Scheldt polders in the north of Belgium from the Late Glacial – early Holocene to the present time, and the effects of this changing landscape on the human settlement. The regional landscape evolution has been visualised in a series of palaeogeographical maps for successive time frames. Two different map series were produced: a series of Holocene palaeogeographical reconstructions (11, 000–950 cal BP) based on geotechnical, geological and archaeological data, and a series of post-Medieval landscape reconstructions (16th- to 19th-century) based on historical maps, land registers and soil data. Additional palaeoenvironmental information from fossil pollen and plant remains allowed reconstruction of the vegetation and wetland changes, particularly for the middle to late Holocene. Peat growth was the main key to understanding the landscape evolution of the Waasland Scheldt polders. Whereas the landscape evolution during the Holocene was mainly sea-level driven, the transformation of the landscape during the last millennium was largely due to human interventions.